Dendrimer pre-treatment enhances the skin permeation of chlorhexidine digluconate: characterisation by in vitro percutaneous absorption studies and time-of-flight secondary ion mass spectrometry - Holmes, Amy M.; Scurr, David J.; Heylings, Jon R.; Wan, Ka-Wai; Moss, Gary P. (Elsevier, 2017)
Skin penetration and localisation of chlorhexidine digluconate (CHG) within the skin have been investigated in order to better understand and optimise the delivery using a nano polymeric delivery system of this topically-applied antimicrobial drug. Franz-type diffusion cell studies using in vitro porcine skin and tape stripping procedures were coupled with Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS) to visualise the skin during various treatments with CHG and polyamidoamine dendrimers (PAMAM). Pre-treatment of the skin with PAMAM dendrimers significantly increased the amount and depth of permeation of CHG into the skin in vitro. The effect observed was not concentration dependant in the range 0.5 – 10 mM PAMAM. This could be important in terms of the efficiency of treatment of bacterial infection in the skin. It appears that the mechanism of enhancement is due to the PAMAM dendrimer disrupting skin barrier lipid conformation or by occluding the skin surface. Franz-type diffusion cell experiments are complimented by the detailed visualisation offered by the semi-quantitative ToF-SIMS method which provides excellent benefits in terms of sensitivity and fragment ion specificity. This allows a more accurate depth profile of chlorhexidine permeation within the skin to be obtained and potentially affords the opportunity to map the co-localisation of permeants with skin structures, thus providing a greater ability to characterise skin absorption and to understand the mechanism of permeation, providing opportunities for new and more effective therapies.